Komposisi Hasil Tangkapan Ikan di Pelabuhan Pendaratan Ikan (PPI) Jembatan Puri Kota Sorong, Provinsi Papua Barat - Jeremias Rumala Tuhumena; Lindon Robinson Pane; Sendy Lely Merly; Rosa Delima Pangaribuan; Dandi Saleky (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Fish resources are one of the resources that are not only used to meet the needs of daily life, but also to improve people's welfare. Sorong City has one of the largest Fish Landing Ports (PPI) in West Papua Province with its main commodities consisting of 7 types, namely tuna, mackerel, red snapper, squid, grouper, trevally and gutila. The purpose of this study was to determine the composition of fish landed at the Jembatan Puri Fish Landing Port. The purposive sampling method is used for fishermen along with the fish caught. The results of this study are that the composition of fish species consists of 6 types (Yellowfish, Skipjack, Lemadang, Red Snapper, Bigeye Tuna and Black Setuhuk) with each type composition of 32%, 33%, 3%, 28%, 3%. , and 1%. The weight composition of each type of fish obtained is 29%, 25%, 5%, 10%, 19%, 12%. With the highest composition of fish species, namely Cakalang fish and the lowest, namely black setuhuk fish, while for the highest weight composition, Maddihang fish, while the lowest is Lemadang fish.